On the autonomy of the concept of disease in psychiatry - Schramme, Thomas (Frontiers in Psychology, 2013)
Does the reference to a mental realm in using the notion of mental disorder lead to a dilemma that consists in either implying a Cartesian account of the mind-body relation or in the need to give up a notion of mental disorder in its own right? Many psychiatrists seem to believe that denying substance dualism requires a purely neurophysiological stance for explaining mental disorder. However, this conviction is based on a limited awareness of the philosophical debate on the mind-body problem. This article discusses the reasonableness of the concept of mental disorder in relation to reductionist and eliminativist strategies in the philosophy of mind. It is concluded that we need a psychological level of explanation that cannot be reduced to neurophysiological findings in order to make sense of mental disorder.